1997
DOI: 10.1128/jvi.71.11.8602-8614.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the herpes simplex virus type 1 ICP0 C3HC4 zinc ring finger reveals a requirement for ICP0 in the expression of the essential alpha27 gene

Abstract: The herpes simplex virus type 1 (HSV-1) immediate-early (IE) protein ICP0 has been implicated in the regulation of viral gene expression and the reactivation of latent HSV-1. Evidence demonstrates that ICP0 is an activator of viral gene expression yet does not distinguish between a direct or indirect role in this process. To further our understanding of the function of ICP0 in the context of the virus life cycle, site-directed mutagenesis of the consensus C 3 HC 4 zinc finger domain was performed, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 78 publications
(149 reference statements)
2
46
0
Order By: Relevance
“…To exclude the possibility that RHG120 has secondary mutations other than the C116G/C156A substitutions that may affect ICP0 translocation, we adopted a previously characterized RFm virus (21,24). Both RHG120 and the RFm virus contain the same C116G/C156A substitutions in ICP0, but RHG120 was constructed by a bacterial artificial chromosome (BAC) containing the genome of HSV-1(F) (18), whereas RFm was generated by a conventional recombination method with an ICP0-null virus derived from HSV-1 strain 17 (24). The results also showed effective translocation of ICP0 from the RFm virus containing the C116G/C156A mutations in the presence of PAA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To exclude the possibility that RHG120 has secondary mutations other than the C116G/C156A substitutions that may affect ICP0 translocation, we adopted a previously characterized RFm virus (21,24). Both RHG120 and the RFm virus contain the same C116G/C156A substitutions in ICP0, but RHG120 was constructed by a bacterial artificial chromosome (BAC) containing the genome of HSV-1(F) (18), whereas RFm was generated by a conventional recombination method with an ICP0-null virus derived from HSV-1 strain 17 (24). The results also showed effective translocation of ICP0 from the RFm virus containing the C116G/C156A mutations in the presence of PAA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the reduced ICP4 and ICP27 mRNA levels in the presence of the LATs might be a consequence of reduced ICP0 mRNA levels. Indeed, it was shown that, in the absence of structural viral proteins such as Vmw65 (10) and at a low MOI, ICP0 can activate the expression of ICP4 and ICP27 genes (10,30,36). Further experiments are in progress to address the mechanism of action of the LATs upon ICP0, ICP4, and ICP27.…”
Section: Discussionmentioning
confidence: 99%
“…We chose initially to examine the influence of the LATs on ICP0 expression for the following reasons. (i) ICP0 is the first IE gene to be expressed at very early times postinfection (36). (ii) This IE protein is a transactivator which enhances HSV-1 replication during acute infection as well as reactivation from latency (9) and is capable of activating all three kinetic classes of HSV genes (10).…”
Section: ͻ4 ͻ4mentioning
confidence: 99%
“…HSV-1(F) is a limited-passage isolate described before (79). The properties of the ΔICP0, R7914, ICP0 Ring Finger (RF), ΔICP27, ΔICP8, R2621 (ΔVHS), ΔUL46, and R3616 mutant viruses were described elsewhere (35,40,(80)(81)(82)(83)(84)(85).…”
Section: Methodsmentioning
confidence: 99%